Investigation of The Effect of Concurrent Training Strength and Endurance Training on Physical, Physiological and Psychological Parameters in Young Football Players - PINAR, SALİH (LAHORE MEDICAL RESEARCH CENTER LLP, 2021)
Background: Football is a versatile team sport that requires a range of physical characteristics, including flexibility, power, strength, endurance, speed, repetitive sprinting, quickness-agility and technique-tactics. Developing all these features at the same time, especially in the pre-season, when players are in a deconditioning state, returning to training after a rest period; it is quite difficult for coaches and performance trainers. Aim: The aim of this study is to examine the effects of strength and endurance training applied simultaneously on some physical, physiological and psychological parameters in young football players. Methods: U19 age group players were included in the research group, 24 male football players who played amateur or professionally licensed football for at least 5 years and trained for an average of 2 hours a day, 5 days a week; (Endurance+Strength Group n=12, Strength+Endurance Group n=12). In the study, 1 RM strength test, agility, speed, technique, decision-making skills and endurance tests were taken from the participants. In our study, with the pretest-posttest measurement method; Yo-Yo test, Loughborough Soccer Passing Test (LSPT), Illinois Agility Test, 30 meters Speed Test, Maximal (1RM) Strength Test, Jumping Test (CMJ) were applied. Results: The findings obtained when the performance values of football players within and between groups were evaluated statistically; It has been determined that the positive increase in endurance, strength, sprint, agility/speediness, jump and lspt pass test values as a percentage (%) was seen in the group that applied strength training before endurance training. Conclusion: The application of strength training before endurance training in 'concurrent' training model applications in young football players; on performance values; It has been determined that endurance training has more effect than applying it before strength training. According to these results, it is thought that designing the programs by taking this situation into consideration in the training program adjustments can contribute more to the coaches and the player group in terms of sportive efficiency.
Keywords: Football; concurrent; strength; endurance; LSPT; SOCCER PLAYERS; PERFORMANCE; DRILLS; ELITE; INTERFERENCE; INTENSITY